Time to wait and hope. (Journal of Parents and Teachers, 2016)
The following article deals with Christmas. It reviews the characteristics and events that happen in this time. In addition, it reflects about the festivity’s value and everything that people, even parents or children wait or hope for it.
Keywords: Education; hope; Christmas; festivity; values.